Macro and bank specific determinants of nonperforming loans in polish commercial banks - Petkovski, Mihail; Kjosevski, Jordan; Jovanovski, Kiril (Publishing House of Wroclaw University of Economics and Business, 2021)
The aim of this paper was to examine the determinants of non-performing loans (NPLs) in Polish commercial banks, and investigate the bank specific and macroeconomic determinants of NPLs for a panel of 18 banks from Poland, using annual data for the period 2005-2018. The authors applied four alternative estimation techniques: the fixed effects model, the random effects model, the difference Generalized Method of Moments and the system Generalized Method of Moments. The analyses show the bank-specific determinants, with the impact on the amount of NPLs including greturn on equity and growth of gross loans, while from the macroeconomic determinants the most important factors are: GDP growth, domestic credit to private sector, public debt and unemployment.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 107-126
Keywords: non-performing loans; macroeconomic determinants; bank-specific determinants; Poland; Generalized Method of Moments